The challenges and strategies of Islamic school mentor teachers in implementing ELT lesson plans - Saiful Akmal; Fitriah Fitriah; Intan Fadhilah (Studies in English Language and Education, 2022)
The availability of the lesson plans as organized guidance for teachers is critical in achieving the objectives of English Language Teaching (ELT) in policy decisions, curriculum planning, and classroom implementations. However, it is unavoidable if teachers experience difficulties generating lesson plans, necessitating specific strategies to deal with the situation. This study aims to examine the challenges faced by state Islamic secondary school English mentor teachers in implementing lesson plans and the strategies they utilized to overcome those challenges. This study employed a qualitative research design utilizing data purposively gathered from the semi-structured interviews involving five English school mentor teachers from State Islamic Secondary School No. 4 in Banda Aceh. The findings revealed that teachers’ most significant challenges in implementing lesson plans were time constraints, format changes, administrative burdens, and students’ lack of interest. The study also found out that attending the MGMP (Musyawarah Guru Mata Pelajaran, or the Teachers Professional Development Forum), using a guidebook, asking for advice from colleagues, and using the internet as a learning resource are common strategies the teachers used in overcoming their challenges. It is expected that the impact of this study provides a practical and critical reflection to develop a more realistic and workable ELT lesson plan implementation for mentor teachers amidst their demanding roles and increased administrative responsibilities. This study also recommends that university/faculty administrators and lecturers be more attentive to courses related to lesson plan design, such as English Curriculum Design, English Course Design, and Micro Teaching.